Characteristics of iodine-bearing silver-impregnated alumina sorbents and their direct solidification via hot isostatic pressing - Sakuragi, Tomofumi; Yoshida, Satoshi; Kato, Osamu (Frontiers in Chemistry, 2023)
Waste management for radioiodine is a key issue for the sustainable nuclear fuel cycle. The iodine adsorption behavior on a bed column of a silver-impregnated alumina sorbent (AgA) under conditions designed to match those of the Rokkasho reprocessing facility dissolver off-gas (DOG) system was investigated using different volatilized iodine concentrations. Cross-sectional observations of iodine-bearing AgA grains revealed that iodine was adsorbed as silver iodide and silver iodate, and gradually distributed from the surface to the inside of the AgA. The iodine distribution throughout the AgA beds allowed us to estimate the length of the mass-transfer zone. This suggests that the iodine load fraction in AgA (adsorbed iodine/total impregnated silver) will be averaged to 50% in the expected facility equipment design. This study also describes the waste form durability after disposal. To reproduce the average iodine loading in the waste form, 100%-loaded AgA grains were mixed with an equal amount of commercially available alumina reagents and consolidated through hot isostatic pressing at 175 MPa and 1,325°C for 3 h. The resultant 50%-loaded solid was used for the static leaching test over 4.5 years, where the leached iodine was less than 0.2% under simple reducing conditions. This suggested that the HIPed solid of AgA from Rokkasho DOG showed preferable water resistance for after disposal safety.